PERAN PBB ATAS PELANGGARAN HAM TERHADAP SUKU UIGHUR DI PROVINSI XINJIANG, REPUBLIK RAKYAT CINA (RRC) BERDASARKAN INSTRUMEN-INSTRUMEN HAM INTERNASIONAL - Wisye Anabella Alexandra Tumengkol; Amad Sudiro (Jurnal Hukum Adigama, 2022)
Human rights violations are the abuse of power and/or state omission of individual rights,indigenous peoples' rights, refugee rights, and minority group rights. The United Nations, which isa forum that facilitates the resolution of problems in the international community for the sake ofthe continuity of world peace by the objectives of the birth of the United Nations, is expected anddemanded to be able to play an active role in upholding human rights and upholding naturalhuman rights. This research aims to analyze the human rights violations in Xinjiang by theChinese Government against the Uighurs. Some examples of human rights violations committedinclude re-education camps, detention, persecution of ethnic or religious groups, and sexualviolence. This study examines, How is the Chinese Government's compliance with internationalhuman rights instruments that have been ratified regarding cases of human rights violations by theChinese Government against the Uighurs in the Xinjiang Autonomous Region and what theresponsibility of the United Nations in resolving the problem of human rights violations in theXinjiang Autonomous Region. The research method used is normative legal research, descriptiveanalysis, data collection techniques library research, The data processing technique is the statuteapproach, and Methods Data analysis is qualitative. The theories used in this research are stateresponsibility, human rights, law enforcement, non-intervention, and self-determination.